2007
DOI: 10.1073/pnas.0606880104
|View full text |Cite
|
Sign up to set email alerts
|

Reconfiguration of yeast 40S ribosomal subunit domains by the translation initiation multifactor complex

Abstract: In the process of protein synthesis, the small (40S) subunit of the eukaryotic ribosome is recruited to the capped 5 end of the mRNA, from which point it scans along the 5 untranslated region in search of a start codon. However, the 40S subunit alone is not capable of functional association with cellular mRNA species; it has to be prepared for the recruitment and scanning steps by interactions with a group of eukaryotic initiation factors (eIFs). In budding yeast, an important subset of these factors (1, 2, 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
2
19
0
2
Order By: Relevance
“…This conformation would likely promote mRNA binding and allow the ribosome to move more easily across the mRNA. A similar result was achieved in a cryo-EM reconstruction of the 40 S subunit bound to eIF1A and the multifactor complex (MFC), which is composed of eIF1, eIF3, eIF5, and TC (27). These results are consistent with earlier hydroxyl radical cleavage studies that suggested that structural changes occur in the mRNA binding region of the ribosome upon association of eIF1 (28).…”
Section: Searching For the Start Codonsupporting
confidence: 80%
“…This conformation would likely promote mRNA binding and allow the ribosome to move more easily across the mRNA. A similar result was achieved in a cryo-EM reconstruction of the 40 S subunit bound to eIF1A and the multifactor complex (MFC), which is composed of eIF1, eIF3, eIF5, and TC (27). These results are consistent with earlier hydroxyl radical cleavage studies that suggested that structural changes occur in the mRNA binding region of the ribosome upon association of eIF1 (28).…”
Section: Searching For the Start Codonsupporting
confidence: 80%
“…Rotation of the head was also observed in cryo-EM reconstructions of eukaryotic 40S subunits on binding to internal ribosome entry sites (IRESs) of viral mRNAs (Spahn et al 2001b(Spahn et al , 2004b or to the multifactor complex of yeast, comprised of eIF3, eIF1, eIF5 and TC, and eIF1A (Gilbert et al 2007). It is intriguing that the C934T Gcd − mutation we obtained alters the unpaired residue at the base of h28 that serves as the pivot point for head rotation in 70S complexes (Schuwirth et al 2005).…”
mentioning
confidence: 85%
“…This technological platform is beginning to enable investigators to fit genetic and biochemical knowledge into a structural context. For example, whereas there is a wealth of genetic and biochemical information pertaining to translation initiation in yeast, cryo-EM studies are revealing specific structural rearrangements in the 40 S subunit consequent to binding and release of specific initiation factors (14,15). Similarly, cryo-EM methods are illuminating the details of the interactions between the ribosome and the signal recognition particle (reviewed in Ref.…”
Section: Structural Biologymentioning
confidence: 99%